Anti‐EGFR scFv tetramer (tetrabody) with a stable monodisperse structure, strong anticancer effect, and a long in vivo half‐life. Issue 6 (16th May 2016) - Asano, Ryutaro; Koyama, Noriaki; Hagiwara, Yasuyo; Masakari, Yosuke; Orimo, Ryota; Arai, Kyoko; Ogata, Hiromi; Furumoto, Shozo; Umetsu, Mitsuo; Kumagai, Izumi
Abstract : The development of single‐chain variable fragments (scFvs) as therapeutic agents has the potential to reduce the high cost of antibody production, but the development process often impairs scFv functions such as binding affinity and pharmacokinetics. Multimerization is one strategy for recovering or enhancing these lost functions. Previously, we constructed several antiepidermal growth factor receptor (EGFR) scFv multimers by modifying linker length and domain order. Antitumor effects comparable with those of the currently approved anti‐EGFR therapeutic antibodies were observed for scFv trimers. In the present study, we fractionated an anti‐EGFR scFv tetramer from the intracellular soluble fraction of an Escherichia coli transformant. Compared with the trimer, the tetramer showed higher affinity, greater cancer cell growth inhibition, and prolonged blood retention time. Furthermore, the tetramer did not dissociate into the trimer or other smaller species during long‐term storage (up to 33 weeks). Thus, our developed scFv tetramer is an attractive candidate next‐generation anti‐EGFR therapeutic antibody that can be produced via a low‐cost bacterial expression system. Abstract : We successfully prepared an anti‐EGFR scFv tetramer from the intracellular soluble fraction of an Escherichia coli transformant. Compared with the trimer, the tetramer showed higher affinity, greater inhibition of cancer cell growth, and prolonged blood retention time. Furthermore, the tetramer did not dissociate into the trimer or other smaller species during long‐term storage.